Fiscal Autonomy as the Missing Pillar of Village Governance: Lessons from the French Commune for Indonesia’s Rural Reform - Josepus J. Pinori; Irwansyah Irwansyah; Donna Okthalia Setiabudhi; Ahsan Yunus; Toar K.R. Palilingan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This article offers a comprehensive and original examination of village autonomy in Indonesia by juxtaposing it with the Commune governance model of France, highlighting a critical gap rarely addressed in existing scholarship: the absence of fiscal autonomy as the core determinant of genuine local self-governance. While Indonesia’s Village Law formally recognizes autonomy, it remains predominantly grant-based and structurally dependent on central transfers, producing a paradox wherein villages possess political authority but lack sustainable fiscal capacity. Employing a comparative normative analysis grounded in fiscal federalism, subsidiarity, and public choice theory, the study reveals that Indonesia’s system embeds vertical control through ex-ante supervision, rigid expenditure menus, and limited revenue-raising powers. In contrast, French Communes enjoy constitutionally protected inherent autonomy, broad compétence générale, and—most importantly—robust local taxing powers that anchor accountability, policy innovation, and local economic dynamism. The article’s key contribution lies in proposing a Tiered Village Fiscal Autonomy Model, a reform blueprint that adapts the Commune principles without replicating them. This study demonstrates that Indonesia’s future village governance requires shifting from transfer-driven development to a self-financing, autonomy-strengthening system that enhances accountability and community participation. By offering a normative, comparative, and policy-oriented framework, the article provides a novel and actionable pathway for reimagining village autonomy in Indonesia toward stronger local governance and sustainable development.